Peran PERAN APLIKASI TEKNOLOGI DALAM MENYEIMBANGKAN PERMINTAAN DAN PENAWARAN: SINTESIS STUDI LITERATUR TERKINIAplikasi Teknologi dalam Menyeimbangkan Permintaan dan Penawaran: Sintesis Studi Literatur Terkini - Nugraha, Rahmat Taufik; Saeppani, Asep; Guntara, Agun; Al-Amin, Al-Amin (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research explores the role of technology applications in balancing supply and demand in the global market through a synthesis of recent literature studies. Information and Communication Technology (ICT) such as e-commerce, big data analytics, and other digital platforms have shown significant roles in enhancing market efficiency. E-commerce facilitates consumers in obtaining products quickly and enables sellers to reach broader markets, reducing geographical barriers. Big data and AI technologies assist in demand prediction and inventory management, while IoT and blockchain improve transparency and efficiency in the supply chain. Although these technology applications offer numerous benefits, challenges such as significant investments, the need for specialized skills, and issues of data security and privacy remain substantial barriers. This research concludes that the appropriate application of technology can support the balance of supply and demand, improve market efficiency, and contribute to sustainable economic growth. Continuous evaluation and the development of adequate technological infrastructure are necessary to fully leverage the potential of technology in the modern economy.